EFFECTIVENESS OF ANTIOXIDANTS AS BROWNING INHIBITORS AGAINST SHOOT Cyrtostachys renda AS CALLUS CULTURE EXPLANT - Syamsurizal, Syamsurizal; Utami, Diah Tri; Elisma, Elisma; Lizawati, Lizawati; Sasongko, Aries Bagus; Prabowo, Beni Hendro (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Cyrtostachys renda has various pharmacological activities. C. renda roots contain alkaloids and flavonoids as secondary metabolites' main components responsible for anti-inflammatory and anticancer activities. To produce secondary metabolites from C. renda, tissue culture can be used through callus and cell suspension culture techniques. Browning is one of the main challenges in plant tissue culture, which inhibits the success of callus formation, especially in plants with a high content of phenolic compounds such as C. renda. This study tested the effect of soaking in polyvinylpyrrolidone (PVP) and ascorbic acid (AA) in inhibiting the browning process in C. renda explants. Explant colour change testing was done in vitro by soaking the explants in five concentrations of PVP and AA (50, 100, 150, 200 and 250 ppm). Changes in explant colour were then analyzed using the Royal Horticultural Society (RHS) colour chart. The results showed that the PVP antioxidant with a concentration of 200 ppm could suppress explant browning until the fourth day. In comparison, explants treated with AA antioxidants with a concentration of 200 ppm showed browning symptoms on the second day. It can be concluded that antioxidants can reduce the browning level in C. renda shoot explants, and the antioxidant PVP can reduce the browning level better than AA. The mechanism of PVP as an anti-browning agent through inhibition of phenolic oxidation. This study's novelty is obtaining the type of anti-browning PVP with an optimum concentration of 200 ppm to inhibit the browning of C. renda shoot explants.